Economic Valuation of Non Timber Forest Products Contribution in Tribal Livelihood in West Singhbhum District of Jharkhand - Singh, Praveen Kumar; Sulaiman Quli, S. M. (Indian Forester, 2011)
The study has been conducted to evaluate the economic dependency of tribal livelihoods and to explore the economic contribution of NTFP in their livelihoods in 50 selected villages of West Singhbhum district of Jharkhand state. The study reveals substantial contribution of NTFP in the tribal livelihoods. Six major NTFPs of this forests, managed under 'Mundari-khuntkattidari' system of traditional management by the Tribals, were included in the present study. The economic returns from NTFP was found to have suffered a lot as a result of some major constraints like- unorganized trade, lack of proper storage and value addition facilities and marketing by The middle men. Besides the economic valuation of NTFPs contribution in tribal livelihoods, the gaps in existing practices and knowledge levels leading to low returns were also identified and factors affecting the profitability were screened with some suggestion to further enhance the economic returns.